The Third Reich in power - Evans, Richard J. (New York : Penguin Books, 2006)
Before Hitler seized power in 1933 Germany had been famous for its sophistication and complexity. So how was it possible for a group of ideological obsessives to re-mould it into a one-party state directed at war and race hate? How did the Nazis win over the hearts and minds of Germany's citizens, twist science, religion and culture, and transform the country's politics to achieve total dominance so quickly? From the Nuremberg Laws to the Olympic Games, Kristallnacht to the Hitler Youth, this account shows how a whole population became enmeshed in a dictatorship that was consumed by hatred and driven by war.
The police state -- The mobilization of the spirit -- Converting the soul -- Prosperity and plunder -- Building the people's community -- Towards the racial utopia -- The road to war.
Originally published: England : Allen Lane, 2005.
Includes bibliographical references (p. [713]-900) and index.
Keywords: Germany -- Politics and government -- 1933-1945.; Nationalsozialistische Deutsche Arbeiter-Partei -- History; Germany -- Economic policy -- 1933-1945.; Hitler, Adolf, -- 1889-1945.; Political persecution -- Germany -- History -- 20th century; Jews -- Persecutions -- Germany